Cerebral Epidural Abscess Secondary to Blastomyces Masquerading as an Epidermoid Tumor. (29th May 2017) - Doberstein, Cody; Noor, Abass; Choi, David; Smith, Jacob; Groh, Darren; Mermel, Leonard; Doberstein, Curtis
Abstract: There have been infrequent reports of isolated central nervous system blastomycosis. We report a case of intracranial epidural abscess secondary to Blastomyces dermatitidis in a patient residing in Rhode Island with a history of remote travel to an endemic area. The clinical, radiographic, and pathologic features of this unique case are reviewed.